2021
DOI: 10.32628/ijsrset218440
|View full text |Cite
|
Sign up to set email alerts
|

Role of ICT4D in the Growth and Development of SMES : A Solution To Digital Divide

Abstract: ICTs have played a critical role within the development of business particularly small and medium enterprises. During a modern digital era, technology is most vital pillar within the provision of data and knowledge for the growth of development, sustainability, productivity and competitiveness of small and medium enterprises. The primary goal of this study was to research on the role of ICT4D in the growth and development of SMEs: a solution to digital divide. The paper used secondary data. It was noted that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The International Monetary Fund (2020), for example, has suggested that supportive policies in the economy can help small and medium enterprises (SMEs) to make the most of digital technologies and outlined the need for supportive macroeconomic and financial policies, including the provision of finance and capacity-building. Furthermore, Benard et al (2021) have also assessed the relationship between SMEs in developing countries and outlined the urgent need to keep SMEs out of the so-called "digital-divide". Unless this problem of slow adoption of technology innovations in Kenyan SMEs is taken seriously and solved, Kenya will not attain its economic growth and development agenda as spelt out in Kenya Vision 2030.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The International Monetary Fund (2020), for example, has suggested that supportive policies in the economy can help small and medium enterprises (SMEs) to make the most of digital technologies and outlined the need for supportive macroeconomic and financial policies, including the provision of finance and capacity-building. Furthermore, Benard et al (2021) have also assessed the relationship between SMEs in developing countries and outlined the urgent need to keep SMEs out of the so-called "digital-divide". Unless this problem of slow adoption of technology innovations in Kenyan SMEs is taken seriously and solved, Kenya will not attain its economic growth and development agenda as spelt out in Kenya Vision 2030.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…According to Febriany et al (2023), MSME owners take advantage of technological developments to increase their competitiveness with various strategies. The research study of Benard et al (2021) explains that small and medium enterprises have an impact on the economy in Kenya. Companies in Kenya, especially SMEs, are already enjoying the benefits and potential of adopting and utilizing ICT in their operations.…”
Section: Information and Communication Technology (Ict)mentioning
confidence: 99%
“…Information technology has been recognized as very useful to small businesses by some governments to such an extent that they have supported their deployment in SMEs [7][8]. Moreover, several SME leaders recognizing the various benefits of technology have embraced it to support the growth of entities under their management [9][10][11].…”
Section: Introductionmentioning
confidence: 99%